2008
DOI: 10.1352/0047-6765(2008)46[93:fdmbtp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Family Decision Making: Benefits to Persons With Developmental Disabilities and Their Family Members

Abstract: Family involvement in planning and choosing services has become a key intervention concept in developmental disability services. This study (N = 547) modeled patterns of family decision making and assessed benefits to persons with developmental disabilities (DDs) and their family members. A latent profile analysis identified 4 classes that were highly involved in decision making (n = 118), involved only in planning (n = 166), involved only in financial decisions (n = 75), and uninvolved (n = 188). Multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Prior research had indicated that family members experience ableism (Opperman & Alant, 2003; Ryan & Runswick-Cole, 2008), yet these prior studies did not examine breadth or nature of settings of ableism. Prior research on empowerment has reflected mainly empowerment within the services system (Caldwell & Heller, 2003; Caldwell, 2006; Neely-Barnes, Graff, Marcenko, & Weber, 2008). This paper contributes to the literature through identifying ways in which empowerment is manifested in community settings as part of a resistance to ableism.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research had indicated that family members experience ableism (Opperman & Alant, 2003; Ryan & Runswick-Cole, 2008), yet these prior studies did not examine breadth or nature of settings of ableism. Prior research on empowerment has reflected mainly empowerment within the services system (Caldwell & Heller, 2003; Caldwell, 2006; Neely-Barnes, Graff, Marcenko, & Weber, 2008). This paper contributes to the literature through identifying ways in which empowerment is manifested in community settings as part of a resistance to ableism.…”
Section: Discussionmentioning
confidence: 99%
“…This is true more generally in the field of developmental disabilities. Indeed, family involvement in planning, choosing, and even shaping services for their children is now a key intervention concept in the field of developmental disabilities, and more highly involved families have been found to show better outcomes [Neely-Barnes et al, 2008]. Family-centered care has become recognized as the standard of practice for children with special needs in health care, early intervention, and education [Dokken and Ahman, 2006].…”
Section: Family Involvementmentioning
confidence: 99%
“…Managing self-directed funding and coordinating support arrangements are more challenging for people with intellectual disability than those without cognitive impairment, particularly in the absence of a strong network of informal support (Neely-Barnes, Graff, Marcenko, & Weber, 2008). To realise the potential cost and anticipated QOL advantages of supported living, more knowledge is required about the factors associated with good outcomes to inform service development, commissioning, and funding bodies.…”
Section: Introductionmentioning
confidence: 99%